Feasibility of using reactive silicate particles with temperature-responsive coatings to enhance the security of geologic carbon storage. (April 2020) - Plattenberger, Dan; Brown, Tyler; Ling, Florence T.; Lyu, Xiaotong; Fitts, Jeffrey; Peters, Catherine A.; Clarens, Andres F.
Highlights: Functionalized particles were developed to plug leaks in geological carbon storage. The particles have calcium silicate cores and temperature sensitive coatings. The approach leverages the subsurface geothermal gradient for targeted reactivity. Experiments demonstrate that reactivity is much higher at lower temperature. Modeling was carried out to understand how these particles might be deployed. Abstract: The large-scale deployment of geologic carbon storage will require minimizing the risk of CO2 leakage. Here we report on a novel strategy to seal leakage pathways by injecting functionalized reactive calcium silicate (CaSiO3 ) particles. The particles consist of a mineral silicate core within a temperature-sensitive Poly( N, N -dimethylaminoethyl methacrylate) coating that limits contact between the core and the surrounding CO2(aq) above a switching temperature making them relatively unreactive deep in the subsurface. If the CO2 leaks to shallower depths and cooler temperatures, the coatings would extend and enable the silicate core to react with CO2(aq) to form solid carbonate precipitates that reduce the permeability of the fracture or flow path. A combined laboratory- and simulation-based investigation was conducted to explore key early-stage research questions related to the feasibility of this leakage management strategy. Sand columns were injected with either coated or uncoated CaSiO3 particles and the permeability was measured before and after exposure to CO2 . Experiments were conducted at 35 °C and 70 °C, a range that spans the switching temperature for the coatings. Results show that at the cooler temperature the coating effectively enabled reaction and permeability reduction. At higher temperatures, the coated particles limited mineral carbonation and the permeability decrease was minimal compared to columns with uncoated particles. The morphology and location of the precipitates provides insight about permeability evolution. Model simulations of 2D radial particle transport from an injection point provided insight into the effects of particle size, coating properties, and concentrations of particles in several representative rock formations.